2018
DOI: 10.1093/gigascience/giy003
|View full text |Cite
|
Sign up to set email alerts
|

Giardia secretome highlights secreted tenascins as a key component of pathogenesis

Abstract: Background Giardia is a protozoan parasite of public health relevance that causes gastroenteritis in a wide range of hosts. Two genetically distinct lineages (assemblages A and B) are responsible for the human disease. Although it is clear that differences in virulence occur, the pathogenesis and virulence of Giardia remain poorly understood.ResultsThe genome of Giardia is believed to contain open reading frames that could encode as many as 6000 proteins. By successfully applying quantitative proteomic analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 41 publications
4
65
0
Order By: Relevance
“…Consistent with this possibility, several of the identified proteins without transmembrane regions or palmitoylation sites are translational factors associated with the endoplasmic reticulum. Alternatively, biotin labeling as done in this study may label some secreted proteins since a number of the identified proteins overlap those found in studies of the secretome of G. lamblia (41,63).…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with this possibility, several of the identified proteins without transmembrane regions or palmitoylation sites are translational factors associated with the endoplasmic reticulum. Alternatively, biotin labeling as done in this study may label some secreted proteins since a number of the identified proteins overlap those found in studies of the secretome of G. lamblia (41,63).…”
Section: Discussionmentioning
confidence: 92%
“…Cathepsins-B from Giardia are known to play a role in host-parasite interaction. Several orthologs have been demonstrated to be excreted (Dubourg et al 2018) and digestion by cathepsins-B of host IL-8 (Cotton et al 2014) and of proteins involved in tight junction of host epithelial cells and several chemokines (Liu et al 2018) have been described. The phylogenetic tree of the cathepsin-B sequences from all 11 Giardia genomes consisted of 9 clades.…”
Section: Discussionmentioning
confidence: 99%
“…A recent finding suggests that the cathepsins from the variable clades indeed have an important function. It was shown that the orthologs from clade 7, GL50803.15564 and GL50581.2036 from genome WB and GS, respectively, have dN/dS values of >26, indicating very strong positive selection (Dubourg et al 2018). This strong selection is not expected when these genes do not have an important function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cause disease; they are not invasive and secrete no known toxins [12]. Recent research suggests that G. intestinalis can secrete a large number of immunomodulatory proteins, possibly regulating host immune responses [13][14][15][16]. However, the mechanisms on how interactions between the host and Giardia either lead to parasite clearance or to disease remain to be understood.Recent studies have shown the importance of different immune cells in giardiasis, where both innate and adaptive immunity seem to play significant roles [17][18][19].…”
mentioning
confidence: 99%